Splenic Vein Embolization Using Coil Anchors and Prophylactic Occlusion of a Hepatofugal Collateral for Hepatic Encephalopathy due to Splenorenal Shunt: Technical Note and Literature Review. (27th March 2013) - Inoue, Masayoshi; Tanaka, Toshihiro; Nakagawa, Hiroyuki; Yoshioka, Tetsuya; Kichikawa, Kimihiko
Abstract : Purpose . Interventional treatment strategies for patients with encephalopathy due to splenorenal shunt remain controversial. Portosplenic blood flow separation by occluding the splenic vein could avoid the complication of severe portal hypertension, but it would require repeated reintervention due to recurrence of symptoms. This paper describes occlusion of the splenic vein using coil anchors and prophylactic embolization of a collateral hepatofugal vessel with no recurrence of hyperammonemia. Materials and Methods . A 51-year-old woman with severe cirrhosis had hepatic encephalopathy due to a large splenorenal shunt. The serum ammonia level was 132 μ g/dL. Via a transileocolic approach, the splenic vein was completely embolized with 0.035-inch metallic coils using coil anchors while preserving the splenorenal shunt. In addition, one of the collateral vessels of the portal vein, the retrogastric vein, was also embolized prophylactically. Results . After this procedure, the serum ammonia level decreased immediately to 24 μ g/dL. The portal venous pressure increased by only 1.5 mmHg. Hepatic encephalopathy had not been observed for 25 months after the procedure, and neither retention of ascites nor worsening of esophageal varices and liver function was observed. Conclusion . This procedure appears to be safe and effective for hepatic encephalopathy caused by a splenorenal shunt.